Syllabus enhancement for electromagnetic course in biomedical electronics engineering at Universiti Malaysia Perlis - Aishah Hartini, Jahidin; Nashrul Fazli, Mohd Nasir; Megat Shahirul Amin, Megat Ali; Saidatul Ardeenawatie, Awang; Zulkarnay, Zakaria; A. F., Mohd Salleh; Nazahah, Mustafa (Springer-Verlag., 2013)
Link to publisher's homepage at www.springerlink.com